Changes in the Intra-Annual Precipitation Regime in Poland from 1966 to 2024 - Joanna Wibig; Joanna Jędruszkiewicz (Atmosphere)
Many studies relate to long-term changes in annual precipitation in Poland, yet most of them were statistically insignificant. The primary objective of this research was to investigate the precipitation regime during the year in the context of climate change, which is more crucial than annual averages from the perspectives of agriculture and plant growth, as well as for the industrial sector and human access to clean water. For this reason, we used daily precipitation data from the Institute of Meteorology and Water Management—National Research Institute from 1966 to 2024. Each month of the study was examined for changes in monthly totals, the number of dry and wet days, precipitation intensities, and extremes. In the cold season, a considerable shift in precipitation patterns was found between November and December, which became drier, and January and February, which became wetter with more intense and extreme precipitation. Pronounced changes were also noticed in April and June, when not only the monthly totals but also the number of wet days and precipitation intensity decreased. These two months, together with winter, are essential for plant growth. On the contrary, July became slightly wetter. Interesting changes were also observed in September, including an increase in dry days and more intense rainfall. With the increase in temperature and changes in the advection of air masses, September became more similar to summer than to autumn months. The key factors driving shifts in precipitation regimes during the year were a warmer atmosphere and changes in circulation patterns.